Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture,, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Méthodologie féministe et anthropologie: une alliance possible - Dagenais, Huguette (Anthropologie et Sociétés, 1987)
Méthodologie féministe et anthropologie : une alliance possible Après un bref énoncé des principes épistémologiques et éthiques qui sous-tendent la recherche féministe et de la stratégie qui en découle dans la poursuite de projets concrets, l'auteure examine les affinités et apports réciproques entre anthropologie et méthodologie féministe puis souligne les contradictions profondes qui, selon elle, rendent problématique actuellement le développement de la recherche féministe en anthropologie. Elle termine en suggérant quelques pistes à suivre par les anthropologues féministes dans un proche avenir.
Keywords: 1900-1999; 1980-1989; amérique du nord; amériques; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; méthodologie; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques

Women, violence and social control - Hanmer, Jalna; Maynard, Mary (Humanities, 1987)
Keywords: amériques; continuum de violences; cours; discipline; europe; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; trs3500; violences; violences conjugales; violences contre les femmes*; états-unis

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis

Female sexual slavery - Barry, Kathleen (New York University Press, 1984)
Keywords: amériques; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; fem9000; lit3220; premier cycle; prostitution; régions géographiques; sciences humaines; sociologie; thématiques; violences; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

Le système - Saint-Jean, Armande (Pour en finir avec le patriarcat, 1983)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Pour en finir avec le patriarcat - Saint-Jean, Armande (Opinions, 1983)
Essai théorique et document journalistique à la fois, Pour en finir avec le patriarcat apporte une réponse sereine et engagée à vos questions de tous les jours
Keywords: 1900-1999; amériques; approches et analyses; classe sociale; cours; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions